High performance CO2-facilitated transport membrane fabricated by compounding amine-terminated dendrimer in composite of polyvinyl alcohol and water-absorbing agent. Issue 12 (2nd December 2021) - Ito, Fuminori; Nishiyama, Yuriko; Sugimoto, Rie; Mori, Misato; Yamada, Hidetaka
Abstract: In this study, a high-performance CO2 separation membrane was fabricated by compounding amine-based additives with composite polymers composed of polyvinyl alcohol (PVA) and water-absorbing agents. First, the separation performances of several different membranes were compared; through this process, it was found that the performance was improved when sodium polyacrylate (PAANa) was added to the membrane-forming solution. The physical properties of the membranes and their constituent materials, such as water absorbency and heat tolerance, were also evaluated. The membrane prepared by compounding amine-based additives with a composite polymer produced from PVA and PAANa demonstrated the best performance. When the membrane prepared by compounding amine-based additives with the composite polymer was used to separate a CO2 –He mixture (80:20 (v/v)), the CO2 /He selectivity of the membrane exceeded 600 at a total pressure of 0.1 MPa and was approximately 200 at a total pressure of 0.7 MPa at 85 °C. Graphical Abstract: UF0001